COVID-19 Pandemic: Impact (Also) on Cardiology: Pandemia COVID-19: Impacto (Também) na Cardiologia - Oliveira, Mário (Gazeta Médica, 2020)
The COVID-19 pandemic involved profound and rapid changes in the functioning of health care services. The interruption of clinical programmed activity during the lockdown period and the significant reduction in visits to emergency departments, due to the fear of COVID-19, led to the postponement of appropriate treatment for potentially serious cardiovascular conditions, despite the normal functioning of the interventional units for acute myocardial infarction and stroke. These factors contributed to the decompensation of different pathologies, probably influencing the observed increase in mortality of elderly population in Portugal during the pandemic. This article stresses the importance of keeping population informed about the importance of hospital emergencies in cardiovascular care, in order to allow for timely intervention and greater benefits in the treatment of myocardial infarction and stroke.